2020
DOI: 10.2196/19471
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Use Home Collection Methods to Provide Specimens for SARS-CoV-2/COVID-19 Research: Survey Study

Abstract: Background Innovative laboratory testing approaches for SARS-CoV-2 infection and immune response are needed to conduct research to establish estimates of prevalence and incidence. Self-specimen collection methods have been successfully used in HIV and sexually transmitted infection research and can provide a feasible opportunity to scale up SARS-CoV-2 testing for research purposes. Objective The aim of this study was to assess the willingness of adults … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 17 publications
6
45
0
Order By: Relevance
“…Nevertheless, biological specimen collection is an important logistic challenge to provide massive testing [ 1–3 ]. The possibility to use self-collected samples for COVID-19 testing offers several advantages, especially to minimize the risk of exposing health-care workers to the virus, since self-collection does not require direct involvement of trained personnel in the sample collection [ 4 , 5 ]. Recently, publications have been shown a similar sensitivity between saliva samples and nasal swabs collected by health-care workers and those collected by a patient for COVID-19 molecular diagnosis, thus providing an important background for the choice of this strategy for surveillance of COVID-19 [ 6–8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, biological specimen collection is an important logistic challenge to provide massive testing [ 1–3 ]. The possibility to use self-collected samples for COVID-19 testing offers several advantages, especially to minimize the risk of exposing health-care workers to the virus, since self-collection does not require direct involvement of trained personnel in the sample collection [ 4 , 5 ]. Recently, publications have been shown a similar sensitivity between saliva samples and nasal swabs collected by health-care workers and those collected by a patient for COVID-19 molecular diagnosis, thus providing an important background for the choice of this strategy for surveillance of COVID-19 [ 6–8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a pandemic scenario, at-home self-collection of samples plays a key role in the surveillance and control of the infection by allowing the patient with clinical suspicion of COVID19 to have access to proper healthcare and quick isolation of the confirmed cases [ 4 , 5 ]. Recently published studies show that 80–85% of individuals infected with SARS-CoV-2 have few or no symptoms, while 15–20% develop more severe disease, often associated with advanced age or other co-morbidities [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, biological specimen collection is an important logistic challenge to provide massive testing (1)(2)(3). The possibility to use self-collected samples for COVID- 19 testing offers several advantages, especially to minimize the risk of exposing healthcare workers to the virus, since self-collection does not require direct involvement of trained personnel in the sample collection (4,5). Recently publications have been showed a similar sensitivity between saliva samples and nasal swabs collected by healthworkers and those collected by a patient for COVID-19 molecular diagnosis, thus providing an important background for the choice of this strategy for surveillance of COVID-19 (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…A survey of more than 1400 adults representing a broad range of sociodemographic groups found a strong preference for research studies that allowed home-based self-collection. 40 Most respondents reported that they would be willing to provide saliva (88%) or throat swab (83%) specimens for research studies if they could be self-collected at home, while fewer would be willing to provide throat swab specimens at drive-through (64%) or clinical (53%) settings. Overall, 69% of respondents reported being more inclined to participate in a study if they were able to collect the specimen at home.…”
Section: Discussionmentioning
confidence: 99%